Divergence in situation awareness and workload. - Endsley, Mica R.; Dixon, Jordan; Endsley, Tristan; Jamrog, David; Smith-Velazquez, Laura; Pfeffer, Avi (Ergonomics, 2025)
Situation awareness (SA) and workload have both received considerable attention over the past several decades. Little research has investigated the relationship between these two constructs however. The present study examines the relationship between workload and SA in a task involving operation of unmanned vehicles performing an inspection task. Overall, an inverse correlation between SA and workload was found, with SA decreasing by approximately 20% as workload increased. Unexpectedly, considerable differences in this relationship across individuals were found, however, with 50% of participants showing a correlation between SA and only one workload measure (subjective or secondary task) and 30% showing no correlation between SA and workload on either measure. Reasons for dissociation within different measures of workload and SA are discussed, as well as potential reasons for individual differences leading to dissociations across these two constructs. Practitioner Summary: This study was conducted to better ascertain the relationship between situation awareness and workload. An empirical study involving unmanned vehicle control for space station operations was conducted. Overall, an inverse correlation between SA and workload was found, however, unexpectedly considerable individual differences were uncovered indicating dissociation in the measures.